Sekolah Berstandar Internasional (SBI) - Misran Sihaloho (Wahdatul Ulum Institute, 2022)
To develop Indonesia students’ abilities and skills are not easy. So the government innovated one school named International Standard School. This is not new now. Many schools develop their school become International School. It is not easy to get International standard for the school. Many criteria should be fulfilled by the school. But Indonesia’s government already made some rules for the International Standard School.